Pengaruh Motivasi dan Disiplin Kerja Karyawan Terhadap Produktivitas Karyawan Pada PT. Cahaya Surya Indah Busana Medan - Lastiar Lumbantoruan (Junal Ilmu Manajemen, 2019)
The Effect of Employee Motivation and Discipline on Employee Work Productivity at PT Cahaya Surya Indah Busana Medan”. Thesis, LMII Medan College of Economics, 2019. This study aims to determine the effect of employee productivity at PT Cahaya Surya Indah Busana Medan. The research method used is a quantitative approach, this type of research is quantitative descriptive. Data collection is multiple linear regression. The population used was 140 people out of 215 employees from the results of determining the sample using random with the formula Slovin, as many as 30 employees for the validity and reliability test and the remaining 110 respondents were used for the study sample. The result showed that motivation (X1) and employee work discipline (X2) variables had a significant effect on employee work productivity (Y). The conclusion of this study is that motivation (X1) and employee work discipline (X2) simultaneously and partially have a positive and significant effect on employee work productivity at PT Cahaya Surya Indah Busana Medan.